Boy X - Smith, Dan, 1970- (New York : Chicken House/Scholastic Inc., 2017)
When twelve-year-old Ash McCarthy wakes up after his father's funeral, he finds that he has been kidnapped to an island off the coast of Costa Rica, caught in the middle of a secret and deadly project named Kronos in which his mother is somehow involved, and he must find a way to save them both--and the only person he is sure he can trust is a Spanish girl his own age named Isabel.
"First published in the United Kingdom in 2016 by Chicken House."
Keywords: Kidnapping -- Juvenile fiction; Survival -- Juvenile fiction; Rescues -- Juvenile fiction; Terrorism -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Conspiracies -- Juvenile fiction; Kidnapping -- Fiction; Survival -- Fiction; Rescues -- Fiction; Terrorism -- Fiction; Mothers and sons -- Fiction; Conspiracies -- Fiction